Immunotherapy for nasopharyngeal cancer—a review - Jain, Amit; Chia, Whay Kuang; Toh, Han Chong (Chinese Clinical Oncology; Vol 5, No 2 (April 19, 2016): Chinese Clinical Oncology (Nasopharyngeal Carcinoma-Guest Editors: Joseph Wee, Yoke-Lim Soong, Melvin Chua), 2016)
Nasopharyngeal carcinoma (NPC) is associated with the Epstein-Barr virus (EBV) and characterized by peritumoral immune infiltrate. Advanced NPC has high lethality. Immunotherapy directed against EBV antigen targets has been previously explored in clinical trials, and is likely to be validated as an important target in NPC as randomized data emerges in the future. Cancer vaccines and adoptive T cell therapy have been explored in the clinic, with the latter showing the greatest success. Recent advances in gene sequencing technology now allow personalized tumor epitope mapping, whilst the advent of immune checkpoint inhibitors targeting the PD-1/PD-L1 axis offers the opportunity to activate adaptive T cell response in vivo. Anti-PD1 antibodies have shown promising activity in early phase clinical trials, and randomized studies against chemotherapy are underway. As immunotherapy is incorporated into standard treatment paradigms, issues of optimal combinations with targeting agents, immune adjuvants, and sequence with chemotherapy and radiation therapy will need to be addressed. Effective strategies to increase tumor antigenicity, improve immunological memory and reduce immune escape, will need to be developed to improve treatment outcomes. Here we present a brief history of the evolution of immunotherapy in NPC, and highlight key concepts relevant to its further development in the clinic.